The Relationship Between Public Awareness and Communication, Education, and Information Regarding Earthquake and Tsunami Preparedness in Padang City, Indonesia - Ade Ria Nofrianti; Noli Papertu ENGLARDI (RADINKA JAYA UTAMA PUBLISHER, PADANG, INDONESIA, 2026)
Padang City is a coastal area in West Sumatra categorized as a high-risk zone for earthquakes and tsunamis. Community preparedness is deeply determined by the community's disaster awareness and the effectiveness of disaster Communication, Education, and Information (CEI). Objective: This study aimed to analyze the relationship between public awareness and CEI with household preparedness to face earthquakes and tsunamis in Padang City. Methods: This quantitative study employed a cross-sectional approach, conducted from March to June 2025. The population comprised household heads in Padang City, with a sample size of 105 families selected through multi-stage random sampling. Data were collected via structured interviews using a validated questionnaire and analyzed using univariate and bivariate analysis (Chi-Square test). Results: The univariate analysis showed that 72.4% (76) of respondents were prepared, 76.2% (80) had a good level of awareness, and 66.7% (70) received good CEI. The bivariate analysis showed a highly significant relationship between CEI and household preparedness in facing earthquakes and tsunamis in Padang City (p = 0.000; p < 0.05). Conclusion: Public preparedness is significantly related to the optimization of disaster CEI. It is highly recommended that local emergency authorities actively deliver periodic simulations and structured disaster education campaigns.